O atendimento humano no incentivo ao uso de caixas eletrônicos em agências: um modelo de avaliação quantitativa: estudo de caso em um banco de varejo brasileiro - Oliveira, Marcos Henrique Garro de (2005)
The purpose of this study is to analyze quantitative data to help the understanding of the influence of personal service in the transaction migration from human tellers to ATMs (automatic teller machines), complementing several qualitative researches that can be found in literature about the consumer behavior when facing the intensification of automation in the banking delivery channels and its consequent depersonalization. The relation cause-effect between investments in employees dedicated to the help of ATMs users and the increasing of the transactions in this channel was investigated through a case study in a retail Brazilian bank. The transaction migration to ATMs behavior was analyzed and a model of evaluation of investments in human service was developed and applied considering the measurable gains when reducing the transaction costs in the bank channels. It’s important to emphasize that there is a little amount of evaluation models for investments in banking quality services in literature and this reinforce the relevance of this study. The findings of this research not only contributes to a better comprehension on the role of human service as an incentive to the use of ATMs, as also offer an analysis model for the investments in banking services, which can be used in an evaluation of the exchange gained with the improvement in quality services.